Implementasi Madrasah Diniyah Sebagai Penguat Kurikulum PAI Di SMP PGRI 1 Kasembon Kabupaten Malang - Angga Puji Slamet (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2017)
The purpose of this research is to understand curriculum elaboration through religious learning in SMP PGRI 1 Kasembon. Research method used in this research is qualitative research method. The result of interview, observation, and documentation showed religious learning as big impact to islam education curriculum. Religious learning activity in SMP PGRI 1 Kasembon have positive impact to students especially in their daily pray activity and increase their religious knowledge. Based on research result, next researcher are suggest to: focus more into curriculum elaboration, because this research still stuck in the activities.